Interactive video: a new business medium : The videodisc linked computer for business management - Haynes, T.R. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2022)
The business and industrial worlds have been using videodisc technology over the last decade but recently there has been an upsurge in interest. This upsurge is associated with the possibilities available for linking videodiscs to computers.